The effect of minimum wages on immigrants' employment and earnings - Pia M. Orrenius; Madeline Zavodny (Institute for the Study of Labor (IZA), 2008)
This study examines how minimum wage laws affect the employment and earnings of low-skilled immigrants and natives in the U.S. Minimum wage increases might have larger effects among low-skilled immigrants than among natives because, on average, immigrants earn less than natives due to lower levels of education, limited English skills, and less social capital. Results based on data from the Current Population Survey for the years 1994-2005 do not indicate that minimum wages have adverse employment effects among adult immigrants or natives who did not complete high school. However, low-skilled immigrants may have been discouraged from settling in states that set wage floors substantially above the federal minimum.
urn:nbn:de:101:1-20080527198
Keywords: J23; 330; Immigrants; minimum wage; low-skilled; Mindestlohn; Wirkungsanalyse; Migranten; Ungelernte Arbeitskräfte; Einkommen; Beschäftigungseffekt; USA